Iskanje odgovorov na vprašanja govorjenega jezika - Zemljarič Miklavčič, Jana (Jezik in slovstvo, 2008)
In the paper certain characteristics of spontaneous speech are presented. Particular attention is devoted to those characteristics that according to the traditional notion are considered to be departures from the codification of standard language. I establish that these characteristics also have their own internal logic and that we can seek common laws in them. I also try to determine whether spoken language has its own grammar, and in connection with this how many forms of spoken language there are and what the basis of spontaneous speech is. Amongst semantic and syntactic units I focus on textual actualizers, discourse markers, repetitions, false beginnings, paraphrases, concealed speech and pauses in speaking. I observe these features in material from The Pilot Corpus of Spoken Slovene and attempt to interpret the findings. It will be possible to verify the hypotheses on a reference corpus of spoken Slovene.
Keywords: Corpus linguistics; govorjeni jezik; korpusno jezikoslovje; Slovene; slovenščina